Дослідження кінематичних параметрів руху частинки ґрунту за прямолінійним лезом робочого органа - Тищенко, Сергій Сергійович; Tyshchenko, Sergiy; Швайко, В. Н.; Shvayko, V.; Гурідова, В. О.; Gurіdova, V. (Дніпровський державний аграрно-економічний університет, 2014)
Представлено модель руху частинки ґрунту змінної маси в навколишньому середовищі. Доведено, що в такому випадку, з початком руху частинки після контакту з лезом, нормальна реакція леза знижується, а згодом стає сталою. Одночасно маса частинки збільшується, а її швидкість після контакту з лезом прямує до сталої величини. На відміну від класичної, запропонована модель дозволяє стабілізувати швидкість частинки, хоча на практиці вона досить часто прямує до нуля, а в ідеалі частинка зупиняється (залипання її до леза). Question of the motion of a particle in the environment is very important for agricultural production. This question arises in the design of seeders, at application of fertilizers and other. In agricultural mechanics consider the question about movement of the soil of the blade the cultivator paws, for the descent weeds from the working organs.The soil particle formed after loosening, comes into contact with the edge of the working body, and she starts to move under the influence of the environment. The environment in this case will also be the soil particles. Interaction between the soil particle and the environment leads to the fact that the mass of the particle is changed. The equation of motion of a point with variable mass is equation I.V. Meshcherskiy.Found that the most significant factor is clutch to the particle with the environment, which leads to the increase in mass of the particle. Shown dependences the velocity of the particle V(t), the path S(t), the normal reaction of the blade N(t) and the ratio of the masses m(t) / m0 from the time t and values of the empirical coefficients k1, k2, that characterize including clutch the particle of the soil.Given the model of the motion of a soil particle with variable mass in the environment. Studies show that, in this case, the movement starting particle after contact with the blade, normal reaction of the blade decreases and then remains constant. At the same time, mass of the particle in the interaction with the environment increases and its velocity after contact with the blade, tends to the constant value. The presented model, unlike the classical, allows to stabilize velocity of the particle, although in practice it often tends to zeroю, and ideally particle is stopped (sticking of the particle).
Study of kinematic parameters the motion of the soil particle for rectilinear blade working body
Keywords: частинка ґрунту; soil particle; змінна маса; variable mass; лезо ґрунтообробного робочого органа; edge of soil tillage working organ; рух ґрунту; soil movement; швидкість; velocity; зчеплення; coupling; розпушений ґрунт; down soil